An Introduction to Christianity for a New Millennium - Sinclair, Scott Gambrill (Lanham : Lexington Books, 2008)
This book introduces Christianity without presupposing prior knowledge. It gives a brief, but surprisingly comprehensive, summary of the scriptures, history, doctrines, rituals, and types of Christianity. It also deals with contemporary issues: homosexuality, the role of women, the relationship between faith and science. The Christian author explains what he believes and helps readers discover where they disagree. An Introduction to Christianity for a New Millennium should be useful for Christians and non-Christians.
22 Three Major Types of Christianity23 The Challenge of Modernity; 24 The Feminine in Christian Tradition; 25 Post-European Christianity; Index.
Description based on print version record.
Keywords: Christianity -- 21st century; Christianity -- 21st century; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books